(untitled) (Research, Society and Development, 2022)
Objective: This is a systematic review of articles that study pronation strategies in the last 5 years in intensive care units. Methods: Few articles dealing with this topic were observed, totaling 4 studies out of a total of 143 extracted from the PUBMED databases; SCOPUS; WEB OF SCIENCE; BASE Results: The studies demonstrate similar strategies used in the planning of the technique by professionals who perform pronation, it is also possible to perceive the agreement that pronation in patients with respiratory syndromes hospitalized in intensive care units can be a procedure that acts to reduce the time hospitalization and/or mortality rates, in addition to being able to avoid serious complications. Conclusion: Therefore, it is necessary to emphasize the importance of studies on the subject.